Entrepreneurial Leadership and Sustainable Development—A Systematic Literature Review - Alexandrina Maria Pauceanu (MDPI AG, 2021)
The main aim of this study was to clarify the current literary inconsistencies regarding the characteristics of entrepreneurial leadership and its impact on sustainability. Additionally, another aim was to establish the framework of entrepreneurial leadership and to highlight the main gaps in the entrepreneurial leadership literature. The entrepreneurial leadership literature started to develop recently as a new leadership style that is required to fulfill the current business changes in the fourth industrial revolution. The researchers conducted a narrative literature review to assess the status of entrepreneurial leadership in academia, literature gaps, and the impact of entrepreneurial leadership on the sustainability performance of organizations. Furthermore, the researchers main aim was to investigate the following research question: is entrepreneurial leadership a fixed or a multidimensional concept that differs based on industry, context, and firm size? Regarding the answer to this question, the current study found that entrepreneurial leadership is a multidimensional concept as it is reflected in different perspectives, which indicates the inconsistency of the characteristics of entrepreneurial leadership claimed in the literature. Research limitations—the current study focused on assessing the literature review status of entrepreneurial leadership. Based on that, this study’s limitation is represented in not focusing on testing entrepreneurial leadership’s impact on sustainability either quantitatively or qualitatively. On the contrary, it contributed by analyzing the status of the entrepreneurial leadership literature. Future studies need to further assess this relationship between both concepts and reach an agreement about the common characteristics of entrepreneurial leadership. Originality/value—the current study contributes to the entrepreneurial leadership literature as it highlighted the existing gaps and the inconsistency in the literature. Additionally, it contributed theoretically by connecting entrepreneurial leadership to the existing literature. Furthermore, empirically, it highlighted the contribution of entrepreneurial leadership by emphasizing the impact of it on organizational sustainable development performance. This study represents a call for scholars to focus more on entrepreneurial leadership given its contribution to organizational performance.